SiCnws/CNTs/Cf-C/SiOC composites with multi-scale lossy phases for simultaneous electromagnetic wave absorption and thermal insulation - Bin Ren; Yujun Jia; Hao Chen; Jiaying Ti; Yumeng Deng; Qiang Zhuang; Hejun Li (Journal of Materiomics)
Carbon fiber reinforced carbon-based composites are considered to be an ideal lightweight material with exceptional high-temperature mechanical performance. Nevertheless, their high conductivity result in a strong reflection rather than absorption of electromagnetic wave (EMW) for the stealth application. To address this challenge, a novel carbon-based composite made of multi-scale lossy phases (Carbon nanotubes (CNTs), SiC nanowires (SiCnws), and Carbon fiber (Cf)) and impedance matching phase (SiOC ceramic) was fabricated by the precursor-derived method. The prepared SiCnws/CNTs/Cf-C/SiOC (SCC-CS) composites exhibit an effective absorption (EAB) of 2.4 GHz at a thickness of 1.9 mm and a minimum reflection loss (RLmin) of −58.44 dB (99% absorption) in the X band. The EMW absorption of the composite is attributed to the multiple loss mechanisms and favorable impedance matching with free space, caused by the multi-conductive phase and SiOC in the composite. In addition, the fabricated composites also have thermal insulation properties and can effectively achieve radar cross-sectional (RCS) reduction, which are promising aerospace composites with the integration of structure and function.